The Role of Government and Community Collaboration in the Implementation of Waste Management Policies in Palu City - Ariyadi, Fachriza; Afriandi, Fadli (Journal of Management and Administration Provision, 2024)
Waste management is a crucial issue for the growing city of Palu. Collaboration between the government and the community is the key to effective and sustainable waste management policy implementation. This study aims to describe the collaborative role between the government and the community in the implementation of waste management policies in Palu City. The method used is descriptive, with data collection through observation, in-depth interviews with relevant parties, and analysis of waste management policy documents. The data obtained was analysed qualitatively to provide an overview of the dynamics of collaboration that occurred. The results showed that the Palu City government has played a role in formulating policies, providing waste management facilities and infrastructure, and building a supportive regulatory framework. The government also initiated waste management programmes such as waste banks and temporary disposal sites (TPS)). On the other hand, the role of the community is seen through active participation in these programmes, as well as involvement in waste reduction and recycling activities in their respective neighbourhoods. Nonetheless, challenges are still faced, including the low level of public awareness, the lack of supporting facilities, and inadequate law enforcement. This study concludes that good collaboration between the government and the community is essential in achieving more effective waste management in Palu City. Strengthening collaboration through education, improving facilities, and consistent law enforcement are needed so that waste management policies can be implemented optimally.